Cross-Sectional and Longitudinal Disparities in STEM Career Aspirations at the Intersection of Gender, Race/Ethnicity, and Socioeconomic Status. (November 2018) - Saw, Guan; Chang, Chi-Ning; Chan, Hsun-Yu
Analyzing the nationally representative High School Longitudinal Study of 2009 (HSLS:09), this study examined the cross-sectional and longitudinal disparities in STEM career aspirations at the intersection of gender, race/ethnicity, and socioeconomic status (SES). Results indicated that female, Black, Hispanic, and low SES students were less likely to show, maintain, and develop an interest in STEM careers during high school years. Compared with White boys from higher SES background, girls from all racial/ethnic and SES groups, as well as Black and Hispanic boys from lower SES groups, consistently had lower rates of interest, persistence, and developing an interest in STEM fields.